2011
DOI: 10.1177/104063871102300126
|View full text |Cite
|
Sign up to set email alerts
|

Erysipelothrix Spp. Genotypes, Serotypes, and Surface Protective Antigen Types Associated with Abattoir Condemnations

Abstract: Abstract. The objective of the current study was to investigate characteristics of Erysipelothrix spp. from slaughter condemnations. Specimens from 70 carcasses with lesions suspect for swine erysipelas were collected at an abattoir in Iowa from October 2007 to February 2009. Erysipelothrix spp. were isolated from 59 of 70 carcasses (84.3%). Abattoir inspectors classified lesions as acute, subacute, or chronic; 8 of 8 (100%) were acute cases, 31 of 32 (96.9%) were subacute cases, and 20 of 30 (66.6%) were chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 19 publications
1
44
0
10
Order By: Relevance
“…No significant cross-reactivity against E. tonsillarum strains and E. sp. strain 1 which do not express SpaA, SpaB or SpaC was seen, perhaps suggesting a mechanism for a lack of protection from currently available vaccines (Bender et al, 2011). The above results are consistent with previous observations (Imada et al, 2003) that spa genes are highly conserved among serotypes containing different Spa types, and this characteristic provides a major mechanism for the cross-protective activity of SpaA against challenge with Erysipelothrix spp.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…No significant cross-reactivity against E. tonsillarum strains and E. sp. strain 1 which do not express SpaA, SpaB or SpaC was seen, perhaps suggesting a mechanism for a lack of protection from currently available vaccines (Bender et al, 2011). The above results are consistent with previous observations (Imada et al, 2003) that spa genes are highly conserved among serotypes containing different Spa types, and this characteristic provides a major mechanism for the cross-protective activity of SpaA against challenge with Erysipelothrix spp.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, sera from rabbits hyperimmunized with serotype N, known to express the SpaA protein, were found to be non-reactive against the rSpaA415 polypeptide. However, earlier studies have indicated that serotype N strains lack a type-specific antigen; as a result, they fail to induce antibody production in rabbits (Kucsera, 1973;Wood and Harrington, 1978;Bender et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Since swine erysipelas (SE) reappeared as a clinical problem in pig populations in Japan and in the Midwestern United States, it has been considered as a reemerging disease that contributes substantially to economic losses in the swine industry [1,2,5]. In Japan, to protect against SE, strain Koganei 65-0.15 (serotype 1a), which was attenuated by 65 passages on agar media containing 0.15% of an acriflavine dye, has been used as a seed strain for production of a live vaccine [16].…”
mentioning
confidence: 99%
“…obtained previously [1,3,5,14,18]. Those studies found high rates of serotypes 1a and 2 from pigs with erysipelas from 2007-2009 in Iowa (40.7% and 49.2% of 59, respectively), from pigs affected with erysipelas in Japan from the years 1983-1993 (40.4% and 34.3% of 1046, respectively) [18], from the years 1992-2002 (47.6% and 31.8% of 800, respectively) [5], and from 1994-2001 (28.8% and 47% of 66, respectively) [14].…”
mentioning
confidence: 99%